2019
DOI: 10.24996/ijs.2019.60.12.5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Polycyclic Aromatic Hydrocarbons in Water and Sediments in the Euphrates River, Iraq

Abstract: The monitoring of lotic ecosystems is important for environmental health after war crisis. This study aimed to detect the fate of the sixteen polycyclic aromatic hydrocarbon compounds (PAHs) as priority pollutants in the water and sediment of Al-Hussainya River in Karbala Province. The results indicated that the concentrations in water samples ranged from 0.24–58.72 ηg.L-1 for each of the benzo(a) pyrene and benzo(g, h, i)perylene. The concentrations in sediment samples have been observed to be in a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The findings revealed that heavy metal concentrations in water were higher in the particulate phase than in the dissolved phase. Habeeb et al 14 studied water quality and heavy metals in water, sediment, and aquatic macrophytes in the lotic ecosystem, with the goal of detecting potential environmental effects on the eastern Euphrates drainage in Babylon province .Al-Zughaiby et al 15 determined the correlation between some trace element concentrations in the Euphrates River of Iraq.Based on this research, the rates of concentration of trace element were found in water and soluble form and study sites .Hassan et al 16 studied the distribution of polycyclic aromatic hydrocarbons (PAHs) residues in Euphrates River water and sediment, despite long-standing restrictions on their use and production, the findings indicated that the Euphrates River was contaminated by petroleum hydrocarbons and their residues.Salman and Al-Shammary 17 determined the quality of water in Hilla river by examining many physical and chemical properties .…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed that heavy metal concentrations in water were higher in the particulate phase than in the dissolved phase. Habeeb et al 14 studied water quality and heavy metals in water, sediment, and aquatic macrophytes in the lotic ecosystem, with the goal of detecting potential environmental effects on the eastern Euphrates drainage in Babylon province .Al-Zughaiby et al 15 determined the correlation between some trace element concentrations in the Euphrates River of Iraq.Based on this research, the rates of concentration of trace element were found in water and soluble form and study sites .Hassan et al 16 studied the distribution of polycyclic aromatic hydrocarbons (PAHs) residues in Euphrates River water and sediment, despite long-standing restrictions on their use and production, the findings indicated that the Euphrates River was contaminated by petroleum hydrocarbons and their residues.Salman and Al-Shammary 17 determined the quality of water in Hilla river by examining many physical and chemical properties .…”
Section: Introductionmentioning
confidence: 99%